2018
DOI: 10.1016/j.chempr.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry of Anionic Dimers, Trimers, Tetramers, and Clusters

Abstract: Two or more anions constrained in close proximity within a single pocket are found in a number of natural systems but a less common motif in artificial systems. This review summarizes work on anion receptors capable of stabilizing anionic dimers, trimers, tetramers and clusters in a well-defined fashion. These systems may provide insights into the fundamental chemistry of anion-anion interactions and provide a guide for understanding in greater detail a number of biological and environmental processes, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 136 publications
(121 reference statements)
4
114
0
Order By: Relevance
“…The data crystal was ay ellow prism of approximate dimensions 0.28 mm 0.12 mm 0.10 mm. A single crystal of 2a 2 ·Cl À -TATA + was obtained by vapor diffusiono f n-hexane into as olution in CH 2 ClCH 2 Cl of 2a and 4,8,8, [8a, 15] in a1 :1 molar ratio. The data crystal was an orange prism of approximate dimensions 0.52 mm 0.02 mm 0.01 mm.…”
Section: Methods For Single-crystal X-ray Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The data crystal was ay ellow prism of approximate dimensions 0.28 mm 0.12 mm 0.10 mm. A single crystal of 2a 2 ·Cl À -TATA + was obtained by vapor diffusiono f n-hexane into as olution in CH 2 ClCH 2 Cl of 2a and 4,8,8, [8a, 15] in a1 :1 molar ratio. The data crystal was an orange prism of approximate dimensions 0.52 mm 0.02 mm 0.01 mm.…”
Section: Methods For Single-crystal X-ray Analysismentioning
confidence: 99%
“…Packing structures, along with anion-binding stoichiometries in some cases, can be controlled by the geometriesa nd electronic states of co-existing countercations. [6a, 14] In the presence of the Cl À salt of 4,8,8, cation, [8a, 15] 2a-c also provided[ 2+ +1]-type Cl À complexes, but with relativelyp lanar geometries (Figure 9ii-iv). In 2a 2 ·Cl À -TATA + ,b oth receptor units have disordered pyrrole and thiophene rings in the ratios of 0.68:0.32a nd 0.511:0.489, which shows the presenceo ff our kinds of [2+ +1]-type complexes (Figure 9ii).…”
Section: Ion-pairing Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the field of anion coordinationc hemistry has evolved, new levels of complexity of the related systems have been explored,w hich has increased the need for thorough research of all processes relatedt oa nion coordination. [1][2][3][4][5][6][7][8][9] In this field, urea derivatives have been among the most studied receptors, and numerouss tudies of their complexation with diverse anionic species have been reported. [10][11][12][13][14][15][16][17][18] In pursuit of higher affinity and selectivity,o riginal concepts have been examined with the goal of achieving the desired receptor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore,stabilization of HSO 4 À by complexation with receptors bearing basic moieties in the solid state has always been challenging since the protic oxyanion is susceptible to proton transfer to the host molecules. [7b,d] Hydroxyanions including HSO 4 À are wellknown to dimerize by forming anti-electrostatic, self-complementary (O À H) anion ···O anion hydrogen bonds in crystal structures, [9,10] or are prone to undergo proton transfer to generate SO 4 2À ion, [11] both of which would facilitate the electrostatic contacts with the HB donors due to the pronounced and unitary negative charge density.A saconsequence,t hese competitive processes make co-crystallization of host-guest complexes involving HSO 4 À asignificant challenge.Asearch for structures involving monomeric, pristine HSO 4 À anion in the Cambridge Structural Database (CSD) reveals that numerous HSO 4 À co-crystals have been engineered/reported. Most of these examples are single component systems with undefined or ill-defined binding cavities,inwhich HSO 4 À ions act as solvates to bridge the host molecules;thus,the limited coordinations to the anion found in these complexes likely result from crystal packing (Table S1 in the Supporting Information).Our studies have demonstrated that arylethynyl-based bis-urea derivatives provide ap reorganized, attractive binding pocket for spherical halide anions.…”
mentioning
confidence: 99%